Impact of Biochar and Different Nitrogen Sources on Forage Radish Production in Middle Tennessee (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Short-season forage radish (Raphanus sativus L. var. longipinnatus) has recently gained great popularity in Middle Tennessee and many parts of the world used as a high-quality vegetable crop for human consumption or a forage crop for winter grazing and cover cropping. In this study, we (i) estimated soil pH buffering capacity and microbial activity, (ii) quantified crop productivity influenced by different biochar amendment rates and N fertilizer management practices based on a factorial treatment design. Particularly, biochar was amended at rates of 0, 5, 20, and 40 Mg/ha; N fertilizer was applied at zero (N0), 122 kg/ha of urea (56 kg/ha of N; N1) and 4.8 Mg/ha of aged dairy cattle manure (56-60 kg/ha of N), providing a total of 12 treatments (four biochar rates × three fertilization practices). The combination of biochar and inorganic N fertilizer such as urea appeared to have positive impacts on the short-term biomass production, soil pH buffering capacity, and enhanced soil microbial activity for short-season forage radish production (P < 0.05). Future research is warranted to evaluate the use of biochar in field-based forage/vegetable studies in Tennessee.